Climate Change Induces Shifts in Infectious Disease Dynamics: Emerging Global Threats (World Journal of Experimental Biosciences, 2024)
Climate change and infectious diseases have been topics of interest for professionals such as Environmental Scientists, Ecologists, Public Health professionals, and Social Psychologists. The relationship between climate change and infectious diseases is complex, affecting the environment, social and economic conditions, and human health. It affects pathogens, vectors, transmission routes, and the human population’s susceptibility to diseases. Infectious diseases like malaria, dengue fever, cholera, and influenza are sensitive to climate change, and scientists are focusing on better modeling, preemptive warnings, and new technologies like biosurveillance, artificial intelligence, and vaccine development to reduce the consequences of climate change for new and re-emerging diseases. A combination of multi-level and multi-sectoral efforts and a global approach is required to monitor and respond to future outbreaks. This paper will explore effective measures in preventing diseases related to climate change and the existing scientific evidence to prove its impact on infectious diseases.